2009
DOI: 10.1200/jco.2009.27.15_suppl.9002
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene expression profile in metastatic melanoma and survival to a dendritic cell-based vaccine

Abstract: 9002 Background: Emerging data suggests that features of the melanoma tumor microenvironment may determine the clinical outcome to immunotherapies. We recently have observed a gene expression signature that correlated with a favorable clinical outcome in response to an IL-12-based melanoma vaccine. Increased expression of chemokine genes and T cell transcripts, and decreased expression of genes associated with aggressive tumor biology, were observed in the favorable group. To determine whether these patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These findings suggest that tumors of the inflamed phenotype do not discriminate among various components of the immune response as they can sustain immune effector and immune regulatory functions simultaneously; it is probably the overall balance between the two vectors that determines the ultimate fate of these cancers individual cancers. More recently, the same group identified a similar pattern predictive of favorable outcome in patients vaccinated with dendritic cell loaded with multiple tumor antigen-derived peptides [ 28 ]. Similar findings were observed by GSK-Biologics in non small cell lung cancer and melanoma patients undergoing vaccination with MAGE-3 protein [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that tumors of the inflamed phenotype do not discriminate among various components of the immune response as they can sustain immune effector and immune regulatory functions simultaneously; it is probably the overall balance between the two vectors that determines the ultimate fate of these cancers individual cancers. More recently, the same group identified a similar pattern predictive of favorable outcome in patients vaccinated with dendritic cell loaded with multiple tumor antigen-derived peptides [ 28 ]. Similar findings were observed by GSK-Biologics in non small cell lung cancer and melanoma patients undergoing vaccination with MAGE-3 protein [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“… 51 Inspired by these results, the following study has analyzed the immune gene profiles of the pre‐treatment tumor biopsies from a second vaccine trial, which revealed a positive association between inflamed gene expression profiles and clinical benefits from a DC‐based vaccine. 52 Furthermore, a clinical trial that validating the effectiveness of therapeutic cancer vaccine Theratope in patients with ovarian, breast or colorectal cancer demonstrated the correlations between pre‐existing inflammation and clinical benefits. However, the patients were not screened or stratified according to their pre‐vaccination immune status in the subsequent phase III clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…In one preclinical study of metastatic melanoma, the expression of a subset of chemokines were associated with CD8 + T cell infiltration [ 34 ]. In patients with metastatic melanoma, the expression of T cell markers and chemokines correlated with response to a DC-based vaccine [ 35 ]. Likewise, a pro-inflammatory gene expression profile within the tumor microenvironment was associated with survival following administration of a protein-based vaccine in patients with metastatic melanoma [ 36 ].…”
Section: Reviewmentioning
confidence: 99%